Damage identification of slab–girder structures: experimental studies - Wang, Y.; Hao, Hong (Springer, 2013)
Slab–girder structures composed of steel girder and reinforced concrete slab are widely used in buildingsand bridges in the world. Their advantages are largely based on the composite action through the shear connection between slab and girder. In order to assess the integrity of this kind of structures, numerous vibration-based damage identification methods have been proposed. In this study, a scaled composite slab–girder model was constructed in the laboratory. Some removable shear connectors were speciallydesigned and fabricated to connect the girder and slab that were cast separately. Then, a two-stage experiment including both static and vibration tests was performed. In the first stage, vibration tests were conducted under different damage scenarios, where a certain number of shear connectors at certain locations were removed step by step. In the second stage, two sets of hydraulic loading equipment were used to apply four-point static loads in the test. The loads are increased gradually until concrete slabcracked. The loading histories as well as deflections at different points of the beam are recorded. Vibration test was carried out before and after concrete cracking. Experimental results show that the changes of mode shapes and relative displacement between slab and girder may be two promising parameters for damage identification of slab–girder structures.